Common G-Quadruplex Binding Agents Found to Interact With i-Motif-Forming DNA: Unexpected Multi-Target-Directed Compounds - Pagano, Alessia; Iaccarino, Nunzia; Abdelhamid, Mahmoud A. S.; Brancaccio, Diego; Garzarella, Emanuele U.; Di Porzio, Anna; Novellino, Ettore; Waller, Zoë A. E.; Pagano, Bruno; Amato, Jussara; Randazzo, Antonio (Frontiers in Chemistry, 2018)
G-quadruplex (G4) and i-motif (iM) are four-stranded non-canonical nucleic acid structural arrangements. Recent evidences suggest that these DNA structures exist in living cells and could be involved in several cancer-related processes, thus representing an attractive target for anticancer drug discovery. Efforts towards the development of G4 targeting compounds have led to a number of effective bioactive ligands. Herein, employing several biophysical methodologies, we studied the ability of some well-known G4 ligands to interact with iM-forming DNA. The data showed that the investigated compounds are actually able to interact with both DNA in vitro, thus acting de facto as multi-target-directed agents. Interestingly, while all the compounds stabilize the G4, some of them significantly reduce the stability of the iM. The present study highlights the importance, when studying G4-targeting compounds, of evaluating also their behavior towards the i-motif counterpart.